Better red than dead: Plasticine moths are attacked less under HPS streetlights than LEDs - Seymoure, Brett; Parrish, Tessa; Egan, Kaley; Furr, Malcolm; Irwin, Danny; Brown, Cassie; Crump, Morgan; White, Jeremy; Crooks, Kevin; Angeloni, Lisa (Basic and applied ecology, 2024)
Anthropogenic light at night is growing exponentially while many insect populations are in decline. Many nocturnal insects provide numerous ecosystem services and are attracted to anthropogenic lights at night resulting in decreased fitness, greater mortality and population declines. During twilight and night, moths are depredated by bats and birds, both of which use vision, among other strategies, to detect and prey upon moths. The visual detection of moths by predators is dependent upon the light environment illuminating the moth's body. Effects of anthropogenic light at night can differ drastically with the color (spectral composition) and intensity of light. Currently, high pressure sodium lamps (HPS) and light emitting diodes (LEDs) are common municipal light sources, and these lights differ spectrally, thus altering the visual scene. Most LEDs are broadband (i.e., white) whereas HPS are long wavelength dominant (i.e., amber); both of these light types can alter color perception of prey. To test if moths are more likely to survive under HPS lighting than LEDs and non-lit poles, we used plasticine clay models. Visual model analyses reveal that HPS lamps rendered moths more cryptic against their background than LEDs or ambient urban lighting, albeit with small differences in contrast that may not be biologically relevant. These results indicate that HPS lighting is the most insect-friendly lighting when considering depredation on insects in comparison to LED.